2019
DOI: 10.3390/su12010235
|View full text |Cite
|
Sign up to set email alerts
|

Motivating Sustainable Change in Tourism Behavior: The First- and Third-Person Effects of Hard and Soft Messages

Abstract: Educating and changing consumers´ attitudes towards sustainable and more environmentally friendly holiday choices is often seen as a key challenge for the tourism industry. The primary objective of this study is, therefore, to increase our understanding of psychological mechanisms underlying consumers’ responses to communication that aims to alter their holiday behavior in a more sustainable direction. Drawing on reactance theory, as well as first- and third-person perception effects, we present an experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Indeed, their instructions are fundamental for making workers understand and align with organizational goals and avoid potential conflicts and ambiguity in the workforce when organizations try to promote environmental and sustainable outcomes [12,27]; and (2) assertiveness, from a communication point of view, plays a key role to persuade people and therefore is a fundamental social skill for leaders and managers, particularly when they need to convince, motivate and engage followers to do certain job tasks and adopt more sustainable behaviors [17,28,29]. Furthermore, a recent study has shown that positive language, when expressed assertively, is perceived as encouraging optimism and self-efficacy, which facilitates the promotion of healthier, safer, and more sustainable behaviors [25,30].…”
Section: Ohse Professionals: Linking Assertiveness and Sustainable Behaviorsmentioning
confidence: 99%
“…Indeed, their instructions are fundamental for making workers understand and align with organizational goals and avoid potential conflicts and ambiguity in the workforce when organizations try to promote environmental and sustainable outcomes [12,27]; and (2) assertiveness, from a communication point of view, plays a key role to persuade people and therefore is a fundamental social skill for leaders and managers, particularly when they need to convince, motivate and engage followers to do certain job tasks and adopt more sustainable behaviors [17,28,29]. Furthermore, a recent study has shown that positive language, when expressed assertively, is perceived as encouraging optimism and self-efficacy, which facilitates the promotion of healthier, safer, and more sustainable behaviors [25,30].…”
Section: Ohse Professionals: Linking Assertiveness and Sustainable Behaviorsmentioning
confidence: 99%
“…The use of third-person technique may also trigger the self-others discrepancy phenomenon, also called the third-person effect (TPE) [51]. It is hypothesized that people exposed to persuasive mass media messages will perceive these messages to have more influence on other people than on themselves [52].…”
Section: Third-person Effectmentioning
confidence: 99%
“…Research (Hermundsdottir & Aspelund, 2021) groups companies based on their motivation towards sustainable practices, whereas companies driven by competitiveness practice fewer environmental saving activities and are more oriented towards commercial aspects. Research (Carvache-Franco et al, 2021), (Skeiseid et al, 2020) uses seven dimensions of personal motivation in driving ecotourism; the results provide management guidance to public institutions and information for companies to develop products that meet demand. Consumers' attitudes towards sustainable and more environmentally friendly holiday options are often seen as a significant challenge for the tourism industry.…”
Section: Introductionmentioning
confidence: 99%